Preparation method of wear-resistant and phenolic yellow-resistant water-based gloss oil for clothing hangtags
By leveraging the synergistic effect of waterborne polyurethane/silicone composite base material and functional additives, combined with supercritical CO2 dispersion technology and an online dynamic compensation system, the conflict between abrasion resistance and phenolic yellowing resistance of garment hangtag varnishes has been resolved, achieving the preparation of high-performance and environmentally friendly garment hangtag varnishes.
Patent Information
- Application Number
- CN202511328136.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2025-12-02
AI Technical Summary
Existing water-based varnishes for clothing tags cannot simultaneously meet the dual requirements of abrasion resistance and resistance to phenolic yellowing, and the production process is slow to respond, resulting in unstable performance and difficulty in meeting environmental regulations.
A composite resin base of waterborne polyurethane dispersion and acrylic modified silicone emulsion, combined with functional additives and supercritical carbon dioxide fluid, is used to achieve synergistic improvement of wear resistance and phenolic yellowing resistance through an online dynamic compensation system. Cyclodextrin modified zeolite molecular sieves are used to selectively capture phenolic compounds to construct a network structure that combines rigidity and flexibility.
It achieves high-performance wear resistance and phenolic yellowing resistance within an environmentally friendly water-based system, reduces production energy consumption, meets stringent environmental regulations, improves product qualification rate, and reduces raw material waste.
Smart Images

Figure CN121045906A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of water-based varnishes for garment hang tags, and more particularly to a method for preparing a wear-resistant and phenol-yellow-resistant water-based varnish for garment hang tags. Background Technology
[0002] As a carrier of brand image, clothing hangtags require surface varnishes that possess both high abrasion resistance and resistance to phenolic yellowing, while simultaneously meeting increasingly stringent environmental regulations. However, existing technologies face a fundamental contradiction: improving abrasion resistance necessitates increasing crosslinking density or introducing hard fillers, but this reduces film flexibility and accelerates cracking; conversely, enhancing resistance to phenolic yellowing requires constructing a loose adsorption structure or adding scavenging agents, which weakens abrasion resistance. This performance conflict makes it difficult for traditional water-based varnishes to balance these dual requirements, leading to defects such as chalking and yellowing under long-term use or harsh storage conditions.
[0003] Currently, the industry is attempting to break through the current limitations through two main technological approaches: one is to use highly cross-linked resins to form a physical shielding layer, but this suffers from drawbacks such as high curing shrinkage and susceptibility to microcracks; the other is to add chemical adsorbents to intercept phenolic substances, but this carries the risk of introducing harmful substances or reducing coating transparency. More importantly, traditional production processes rely on offline testing and experience-based adjustments, resulting in a delayed response to formula fluctuations and unstable product performance. Continuously tightening environmental regulations further compress the survival space of solvent-based technologies, while water-based systems, lacking innovative technological support, still struggle to overcome performance bottlenecks.
[0004] Therefore, developing a water-based varnish preparation method that combines high performance, environmental friendliness, and process controllability has become a technological bottleneck that the garment accessories industry urgently needs to overcome. Summary of the Invention
[0005] To address the issue that water-based varnishes described in the background technology cannot simultaneously meet the dual requirements of abrasion resistance and resistance to phenolic yellowing, as well as the problem of slow production process response, this invention provides a method for preparing varnishes for garment hang tags. Through the triple synergy of resin, additives, and process, it overcomes the technical contradiction of conflicting performance; it constructs an online dynamic compensation system to achieve precise process control; and it achieves industrial-grade durable protection within an environmentally friendly water-based system.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A method for preparing an abrasion-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags includes the following steps:
[0008] S1. Add the waterborne polyurethane dispersion and the acrylic modified organosilicon emulsion to the reactor according to the preset mass ratio, and stir under nitrogen protection to form a composite resin base.
[0009] S2. Based on the technical requirements of wear resistance and phenolic yellowing resistance, functional additives are added synergistically and stirred until homogenized;
[0010] S3. Heat to 65-75℃, slowly add the fluorinated acrylate monomer mixture, and simultaneously add the photoinitiator TPO, and carry out in-situ graft polymerization under UV irradiation;
[0011] S4. The mixture is treated with a high-shear disperser, and supercritical carbon dioxide fluid is injected simultaneously.
[0012] S5. Collect parameter data of gloss, abrasion resistance coefficient and phenol yellowing inhibition rate of the sample in real time, and determine whether the sample is qualified based on the parameter data;
[0013] Specifically, step S5 includes the following sub-steps:
[0014] S5.1. Obtain parameter data in real time through an online monitoring system: the parameter data includes gloss, abrasion resistance coefficient and phenol yellowing inhibition rate;
[0015] S5.2 Calculate the difference based on the parameter data and the target threshold:
[0016] Wear resistance deviation δ1 = Wear resistance coefficient - First target threshold
[0017] Phenolic yellowing deviation δ2 = Phenolic yellowing inhibition rate - Second target threshold;
[0018] S5.3. Determine whether the sample is qualified based on the gloss and the difference; if qualified, the final sample is obtained and discharged; if unqualified, proceed to step S5.4.
[0019] S5.4 Calculate the preparation parameter compensation amount based on the difference, and perform the corresponding compensation operation based on the compensation amount, and then repeat steps S5.1-S5.3.
[0020] Preferably, the waterborne polyurethane dispersion to the acrylic modified silicone emulsion in step S1 is in a mass ratio of 5:3; the stirring conditions are 400-600 rpm for 10-15 min, and the nitrogen flow rate is 2-3 L / min.
[0021] Preferably, the functional additives in step S2 include: a) nano-sized silica sol, added at 3-5% of the total weight of the system; b) cyclodextrin-modified β-zeolite molecular sieve with a pore size of 0.6-0.8 nm, added at 1.5-2.5%; and c) a composite light stabilizer composed of hindered amine 770 and benzotriazole UV-326, added at 0.8-1.5%.
[0022] Preferably, in step S3: the fluorinated acrylate monomer mixture comprises dodecafluoroheptyl methacrylate and hexafluorobutyl acrylate in a mass ratio of 3:1; the amount of photoinitiator TPO added is 1.5-2.5% of the total weight of the monomers; and the UV irradiation intensity is 300-400 mW / cm². 2 , wavelength 365nm.
[0023] Preferably, the injection of supercritical carbon dioxide fluid in step S4 meets the following requirements: critical pressure 7.4-8.2 MPa, temperature 35-40℃; injection rate 10-15% / min of system volume; and high shear disperser speed 10000-15000 rpm.
[0024] Preferably, in step S5.2: the first target threshold is an abrasion resistance coefficient of 0.85; the second target threshold is a phenolic yellowing inhibition rate of 92%.
[0025] Preferably, the qualification determination in step S5.3 requires that the following conditions be met simultaneously: δ1≥0, δ2≥0, and gloss ≥94GU.
[0026] Preferably, the compensation operation in step S5.4 includes: when δ1 < -0.05, adding nanodiamond dispersion, the amount added being... When δ2 < -3%, add an ionic liquid phenol scavenger, with the addition amount Q (%) = 0.5 × log (10 × |δ2|).
[0027] Preferably, the ionic liquid trapping agent is 1-butyl-3-methylimidazolium tetrafluoroborate, which, upon addition, synchronously regulates the supercritical CO2 flow rate: when the viscosity change rate is >10% / min, the flow rate increases by 15-20%; when the viscosity change rate is <5% / min, the flow rate decreases by 10%.
[0028] Preferably, in step S5.1: gloss is detected online by a 60° incident angle spectrometer; abrasion resistance coefficient is predicted in real time based on rheometer data and a particle concentration correlation model; phenol yellowing inhibition rate is calculated by measuring the attenuation rate of phenol characteristic peaks using ultraviolet spectroscopy.
[0029] This invention achieves a fundamental breakthrough in both abrasion resistance and phenolic yellowing resistance within an environmentally friendly water-based system through the synergistic effect of waterborne polyurethane / silicone composite matrix design, directional formulation of functional additives, and UV in-situ polymerization. The molecular recognition cavities of cyclodextrin-modified zeolite selectively capture phenolic compounds, and the resulting rigid-flexible network, formed by gradient crosslinking of fluorinated monomers, fundamentally resolves the inherent contradiction between hardness and toughness in traditional technologies. Supercritical CO2 dispersion technology ensures zero agglomeration of nanoparticles, resulting in a protective layer with both high gloss and long-lasting stability. An online dynamic compensation system, based on real-time monitoring data and a deviation-driven algorithm, reduces process adjustment time to a fraction of traditional methods. A functionalized addition mechanism precisely controls additive dosage, significantly improving product yield and reducing raw material waste. The application of UV curing and supercritical fluids significantly reduces production energy consumption, and the water-based system eliminates organic solvent pollution, meeting the most stringent environmental regulations. The final product exhibits excellent adhesion and resistance to environmental aging on various substrates, fully covering core industry standards and providing a cost-effective green protective solution for garment hang tags. Attached Figure Description
[0030] Figure 1 This is a flowchart of a method for preparing a wear-resistant and phenol-yellow-resistant water-based varnish for clothing hang tags according to the present invention;
[0031] Figure 2 This is a flowchart for determining whether a sample is qualified based on parameter data, provided by the present invention. Detailed Implementation
[0032] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are merely some examples or embodiments of this application. For those skilled in the art, these drawings can be applied to other similar scenarios without creative effort. Unless obvious from the context or otherwise specified, the same reference numerals in the drawings represent the same structures or operations.
[0033] It should be understood that the terms “system,” “device,” “unit,” and / or “module” used herein are one way to distinguish different components, elements, parts, sections, or assemblies at different levels. However, if other terms can achieve the same purpose, they may be replaced by other expressions.
[0034] As indicated in this application and claims, unless the context clearly indicates otherwise, the words "a," "an," "an," and / or "the" do not specifically refer to the singular and may also include the plural. Generally speaking, the terms "comprising" and "including" only indicate the inclusion of explicitly identified steps and elements, which do not constitute an exclusive list, and the method or apparatus may also include other steps or elements.
[0035] Flowcharts are used in this application to illustrate the operations performed by the system according to embodiments of this application. It should be understood that the preceding or following operations are not necessarily performed precisely in sequence. Instead, the steps can be processed in reverse order or simultaneously. Furthermore, other operations can be added to these processes, or one or more steps can be removed from them.
[0036] Figure 1 This is a flowchart illustrating a method for preparing a wear-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags according to the present invention. The optimized method for laser marking and optical variable transfer printing includes the following steps:
[0037] S1. Add the aqueous polyurethane dispersion and the acrylic-modified silicone emulsion to the reactor at a preset mass ratio, and stir under nitrogen protection to form a composite resin base. The mass ratio of the aqueous polyurethane dispersion to the acrylic-modified silicone emulsion is 5:3; the stirring conditions are 400-600 rpm for 10-15 minutes, and the nitrogen flow rate is 2-3 L / min.
[0038] In some embodiments, the key to implementing step S1 of this invention lies in the molecular-level synergy between an aqueous polyurethane dispersion and an acrylic-modified silicone emulsion at a mass ratio of 5:3, constructing a stable composite resin matrix under a nitrogen-inert atmosphere. During operation, the aqueous polyurethane dispersion is first injected into the reactor, and the temperature is controlled at 25±2℃ to avoid the risk of emulsion demulsification. Then, the acrylic-modified silicone emulsion is slowly added. The modification feature of this silicone emulsion is that the acrylate groups grafted onto its side chains can provide active sites for subsequent UV polymerization. Nitrogen gas is continuously introduced at a constant flow rate of 2-3 L / min to effectively isolate oxygen from inhibiting the polymerization of unsaturated double bonds, while simultaneously suppressing the formation of foam that is prone to occur in aqueous systems. The stirring process uses a medium speed of 400-600 rpm to ensure that the two phases are fully mixed to form a uniform milky white liquid, while avoiding the destruction of the emulsion micelle structure due to high shear. After 10-15 minutes, the particle size distribution (D90 < 200 nm) is detected by laser scattering instrument to confirm the formation of an interpenetrating network prototype structure with polyurethane as the continuous phase and organosilicon-acrylic block copolymer as the dispersed phase.
[0039] S2. Based on the technical requirements for wear resistance and phenolic yellowing resistance, functional additives are added synergistically, and the mixture is stirred until homogenized. The functional additives include:
[0040] a) Nano-sized silica sol, added at 3-5% of the total weight of the system;
[0041] b) Cyclodextrin-modified β-zeolite molecular sieve with a pore size of 0.6-0.8 nm and an addition amount of 1.5-2.5%;
[0042] c) A composite light stabilizer consisting of hindered amine 770 and benzotriazole UV-326, added at an amount of 0.8-1.5%.
[0043] In some embodiments, after the composite resin base is formed, step S2 implements the synergistic addition of functional additives based on the technical indicators of wear resistance and phenolic yellowing resistance: First, nano-sized silica sol (3-5% of the total system content) is injected into the reaction system. The active silanol groups on its surface, modified by the silane coupling agent KH-570, form a hydrogen bond cross-linking network with the resin carboxyl groups, simultaneously initiating a medium-intensity pre-dispersion to prevent nanoparticle aggregation; then, cyclodextrin-modified β-zeolite molecular sieves (1.5-2.5% addition amount) are added. This molecular sieve, functionalized with hydroxypropyl-β-cyclodextrin, creates a size-matching effect between its 0.6-0.8 nm window cavity and phenolic molecules, constructing selective adsorption channels through host-guest inclusion. Finally, a composite light stabilizer of hindered amine 770 and benzotriazole UV-326 (added at 0.8-1.5%) is introduced. The piperidine group of the hindered amine captures free radicals, while the conjugated triazole structure of the benzotriazole absorbs ultraviolet photons and undergoes energy level transitions, achieving synergistic quenching through energy transfer. The entire feeding process is carried out at a constant temperature of 45-55℃ with a stirring intensity of 800-1000 rpm for 20-30 minutes to achieve dynamic homogenization. At this point, laser particle size analysis shows that the interfacial tension of the three phases drops below the critical value, the rheological curve exhibits typical pseudoplastic characteristics, and the Fourier transform infrared spectrum at 1720 cm⁻¹... -1 The presence of ester bond characteristic peaks confirms that the silica surface coupling agent forms chemical bonds with the resin matrix, creating reaction compatibility conditions for subsequent in-situ polymerization.
[0044] S3. Heat to 65-75℃, slowly add the fluorinated acrylate monomer mixture dropwise, and simultaneously add the photoinitiator TPO. Perform in-situ graft polymerization under UV irradiation. The fluorinated acrylate monomer mixture contains dodecafluoroheptyl methacrylate and hexafluorobutyl acrylate in a mass ratio of 3:1; the TPO photoinitiator is added at 1.5-2.5% of the total monomer weight; the UV irradiation intensity is 300-400 mW / cm². 2 , wavelength 365nm.
[0045] In some embodiments, after homogenization of the functional additives, step S3 involves UV-initiated in-situ graft polymerization to construct a gradient-strengthened structure: the system is heated to 65-75°C to activate the reactivity of the acrylate double bonds in the resin matrix, while maintaining the fluorinated monomer mixture (dodecyl fluoroheptyl methacrylate: hexafluorobutyl acrylate = 3:1) in a low-viscosity flow state. The fluorinated monomer mixture is slowly injected at a rate of 2-3 mL / min using a constant-pressure dropping funnel, with the photoinitiator TPO (added at 1.5-2.5% of the total monomer weight) added simultaneously. The benzoylphosphide structure of this initiator undergoes α-cleavage under 365 nm wavelength irradiation, generating benzoyl and phosphoryl diradicals to initiate a chain reaction. The UV irradiation intensity is precisely controlled at 300-400 mW / cm². 2 Within a certain range, ensuring the free radical concentration half-life matches the monomer droplet acceleration rate, the fluorinated monomer is directionally grafted in the following three stages: First, a fluorocarbon hard segment core layer (contact angle > 110°) is formed on the methacryloyloxy group of the silane coupling agent on the surface of nano-silica; second, a flexible intermediate layer is constructed by copolymerization with the acrylate side chains of the silicone emulsion; finally, an interpenetrating network is formed with the polyurethane backbone. After a continuous reaction of 30-50 min, the reaction is monitored by real-time infrared spectroscopy at 1725 cm⁻¹. -1 The C=C characteristic peak decayed to less than 5% of the baseline, indicating that the double bond conversion rate was >95%. At this point, the system formed a gradient cross-linked topology with fluorine-containing segments as the shell and organosilicon-polyurethane as the core. Its dynamic mechanical analysis showed that the energy storage modulus curve did not change abruptly in the range of -40℃ to 80℃, confirming that the phase interface was completely fused.
[0046] S4. The mixture is treated using a high-shear disperser, with supercritical carbon dioxide fluid injected simultaneously. The supercritical carbon dioxide fluid injection meets the following requirements: critical pressure 7.4-8.2 MPa, temperature 35-40℃; injection rate 10-15% / min of system volume; and high-shear disperser speed 10000-15000 rpm.
[0047] In some embodiments, step S4 achieves ultimate homogenization of the nanosystem through supercritical CO2 synergistic high-shear dispersion: the post-reaction mixture is transferred to a pressure-resistant dispersion vessel, and the temperature is raised to 35-40℃ to bring CO2 to a supercritical state (density 0.7-0.9 g / cm³). 3At a critical pressure of 7.4-8.2 MPa, supercritical CO2 fluid was injected at a rate of 10-15% of the system volume per min. Its near-zero surface tension allowed it to penetrate the nanoparticle interface layer, effectively disintegrating secondary silica aggregates. Simultaneously, high-shear dispersion at 10000-15000 rpm was initiated, generating cavitation at the rotor tip to form microjets with a local pressure difference >50 kPa. This, combined with the diffusion force of supercritical CO2, allowed the cyclodextrin-modified layer on the zeolite molecular sieve surface to fully expand. Under this dual effect, the system viscosity rapidly decreased to the Newtonian fluid range, and online laser monitoring showed that the D50 value sharply decreased from the initial 350 nm to below 100 nm, with a distribution index (PDI) <0.2. After continuous processing for 20-30 minutes, the system was observed to be translucent blue (Tyndall effect intensity angle <15°) through the viewing window of the vessel. The rheometer detected that the intersection of the storage modulus G' and the loss modulus G” was in the frequency range of 1-10 rad / s, confirming the formation of a solid-like stable dispersion system with nano-silica as network nodes and supercritical CO2 plasticized resin as the continuous phase. Its cryo-electron microscopy image showed that the filler spacing was ≤15nm and there was no hard agglomeration, providing a densification basis for the formation of varnish film.
[0048] S5. Real-time acquisition of sample parameters such as gloss, abrasion resistance coefficient, and phenolic yellowing inhibition rate, and determination of sample qualification based on the parameter data. For example... Figure 2 As shown, Figure 2 This is a flowchart for determining whether a sample is qualified based on parameter data, provided by the present invention. Step S5 specifically includes the following sub-steps:
[0049] S5.1. Parameter data is acquired in real time through an online monitoring system: The parameter data includes gloss, abrasion resistance coefficient, and phenolic yellowing inhibition rate. Gloss is detected online using a 60° incident angle spectrometer; the abrasion resistance coefficient is estimated in real time based on rheometer data and a particle concentration correlation model; the phenolic yellowing inhibition rate is calculated by measuring the attenuation rate of phenol characteristic peaks using ultraviolet spectroscopy.
[0050] In some embodiments, step S5.1 achieves real-time closed-loop control of process quality through a multi-sensor online monitoring system: a 60° incident angle spectrometer is used to continuously scan the surface of the varnish, and the gloss value (GU) is output after Gaussian fitting of the reflection spectrum of its halogen light source in the 450-700nm band. This optical characteristic directly characterizes the flatness and phase separation state of the film micro-region; the wear resistance coefficient is calculated in real time based on the dynamic oscillation test data of a high-precision rheometer through an established particle concentration-loss factor (tanδ) correlation model, specifically in the range of 1-100H. The tanδ feature value at 10Hz was extracted from the z-frequency scan. Combined with the previously calibrated nanofiller concentration gradient database (tanδ decreases by 0.12±0.03 for every 1 vol% increase in concentration), the wear resistance coefficient was estimated. The phenol yellowing inhibition rate was detected by online acquisition of the characteristic absorption peak intensity of phenol at 280nm using a deep ultraviolet fiber optic probe. The phenol concentration decay rate (C□ / C0) was calculated according to the Lambert-Beer law, and then the quantitative index was output through a preset inhibition rate conversion algorithm (η=1-2.3×lg(C□ / C0)). The three-channel sensor data were synchronously transmitted to the central processor at a sampling frequency of 5 times per second. After Kalman filtering and noise reduction, a real-time parameter matrix of [gloss, wear resistance coefficient, phenol yellowing inhibition rate] was generated, providing a decision basis for millisecond-level response for dynamic compensation.
[0051] S5.2 Calculate the difference based on the parameter data and target threshold: wear resistance deviation δ1 = wear resistance coefficient - first target threshold; phenolic yellowing deviation δ2 = phenolic yellowing inhibition rate - second target threshold.
[0052] The first target threshold is an abrasion resistance coefficient of 0.85; the second target threshold is a phenolic yellowing inhibition rate of 92%.
[0053] In some embodiments, step S5.2 performs target-oriented deviation calculation based on the real-time parameter matrix: the [wear resistance coefficient, phenolic yellowing inhibition rate] data stream processed by Kalman filtering is obtained from the central processing unit, the mean of its sliding window is extracted as the current effective value, and algebraic difference operation is performed with the preset first target threshold of 0.85 and the second target threshold of 92% respectively. The wear resistance deviation δ1 = real-time wear resistance coefficient - 0.85 characterizes the degree to which the coating's resistance to mechanical damage deviates from the design benchmark. When δ1 < 0, it indicates that the filler network connectivity is insufficient (corresponding to local agglomeration defects > 50 nm observed by TEM); the phenolic yellowing deviation δ2 = real-time inhibition rate - 92% reflects the molecular capture efficiency gap. When δ2 < 0, it indicates that the cyclodextrin cavity is saturated or the ultraviolet shielding is ineffective. This threshold setting stems from previous accelerated aging validation: when the abrasion resistance coefficient ≥ 0.85, the corresponding weight loss in the Taber abrasion test (CS-10 wheel, 1000g load) is ≤ 4mg, meeting the 4H grade requirements of GB / T 23989-2009; the inhibition rate ≥ 92% ensures that ΔE ≤ 1.5 after 72h phenol vapor exposure (complies with the 4 grade standard of FZ / T 50018-2020). The deviation calculation results use δ1 ≤ -0.05 or δ2 ≤ -3% as the compensation trigger boundary. This tolerance design covers the 0.8% measurement uncertainty of the online monitoring system and inherent process fluctuations.
[0054] S5.3. Determine whether the sample is qualified based on the gloss and the difference; if qualified, the final sample is obtained and discharged; if unqualified, proceed to step S5.4. The qualification criteria require that the following conditions be met simultaneously: δ1≥0, δ2≥0, and gloss ≥94GU.
[0055] In some embodiments, step S5.3 performs a three-dimensional collaborative qualification judgment: based on real-time gloss data and calculated deviation values (δ1, δ2), the sample is deemed qualified and discharge is triggered when δ≥0 (wear resistance coefficient not lower than the target threshold of 0.85), δ≥0 (phenolic yellowing inhibition rate ≥92%), and gloss ≥94GU are simultaneously met; if any condition is not met, the process is switched to compensation. The essence of this judgment logic is a triple blockade of the material failure mechanism—δ≥0 ensures that the nanofiller network forms a continuous permeable structure (corresponding to a particle spacing ≤15nm in TEM observation), δ≥0 confirms that the adsorption saturation of cyclodextrin cavities has not exceeded the critical point (FTIR detection 1640cm). - A characteristic peak intensity of phenolic hydroxyl groups < 5% of baseline and a gloss level ≥ 94 GU indicate that the film surface achieves micron-level smoothness (Ra ≤ 0.08 μm as shown by white light interferometer). This three-dimensional threshold constitutes a stable equilateral triangle design domain: a negative deviation of δ1 suggests the easy formation of microcracks under shear stress, a negative deviation of δ2 indicates the formation of phenol diffusion channels, and insufficient gloss exposes phase separation defects. Upon successful judgment, the system automatically initiates the cooling-filtration-filling sequence; otherwise, the defect type is immediately marked and a compensation decision is made.
[0056] S5.4. Calculate the preparation parameter compensation amount based on the difference, and perform the corresponding compensation operation based on the compensation amount. Then, repeat steps S5.1-S5.3. The compensation operation includes: when δ1 < -0.05, adding nanodiamond dispersion, the amount added being... When δ2 < -3%, an ionic liquid phenolic scavenger is added, with the addition amount Q (%) = 0.5 × log(10 × |δ2|). The ionic liquid scavenger is 1-butyl-3-methylimidazolium tetrafluoroborate, which, upon addition, synchronously adjusts the supercritical CO2 flow rate: when the viscosity change rate is >10% / min, the flow rate increases by 15-20%; when the viscosity change rate is <5% / min, the flow rate decreases by 10%.
[0057] In some embodiments, step S5.4 performs defect-targeted compensation: when δ1 < -0.05, a wear-resistant enhancement path is triggered, and... The amount of nanodiamond dispersion replenishment was calculated using an exponential function designed to compensate for percolation breakage in the filler network (a 23% decrease in percolation probability when |δ1|=0.1). After replenishment, diamond nanocrystal nuclei (5-8 nm in diameter) were embedded in the silica network gaps, improving stress dispersion efficiency by 40%. When δ2<-3%, the phenol yellowing repair mechanism was activated. 1-Butyl-3-methylimidazolium tetrafluoroborate ionic liquid was added at Q(%)=0.5×log(10×|δ2|), whose hydrogen bonding energy with phenol reached 45 kJ / mol (molecular dynamics simulation results). The logarithmic function avoided viscosity abrupt changes caused by excessive addition in the low-bias region. The viscosity change rate of the system was monitored in real time after ionic liquid injection: when Δη / Δt>10% / min, the supercritical CO2 flow rate was increased by 15-20%, utilizing its shear thinning effect to inhibit local gelation; when Δη / Δt<5% / min, the flow rate was reduced by 10%, preventing dispersion failure in the low-shear region. After the compensation operation is completed, the S5.1-S5.3 cycle is restarted immediately until the three-dimensional judgment meets the standard, and its closed-loop response time is <3min.
[0058] Unless expressly stated in the claims, the order of processing elements and sequences, the use of numbers and letters, or other names described in this application are not intended to limit the order of the processes and methods of this application. Although various examples have been discussed in the foregoing disclosure of some embodiments that are currently considered useful, it should be understood that such details are for illustrative purposes only, and the appended claims are not limited to the disclosed embodiments. Rather, the claims are intended to cover all modifications and equivalent combinations that conform to the substance and scope of the embodiments of this application. For example, while the system components described above can be implemented by hardware devices, they can also be implemented solely by software solutions, such as installing the described system on existing servers or mobile devices.
[0059] Similarly, it should be noted that, in order to simplify the description of the present application and thus aid in the understanding of one or more embodiments of the invention, the foregoing description of the embodiments of the present application sometimes combines multiple features into a single embodiment, drawing, or description thereof. However, this disclosure method does not imply that the subject matter of the application requires more features than those mentioned in the claims. In fact, the embodiments contain fewer features than all the features of the single embodiments disclosed above.
[0060] For each patent, patent application, patent application publication, and other material such as articles, books, specifications, publications, and documents referenced in this application, the entire contents of that patent are incorporated herein by reference. This excludes historical application documents that are inconsistent with or conflict with the content of this application, as well as documents that limit the broadest scope of the claims in this application (currently or subsequently appended to this application). It should be noted that if there are any inconsistencies or conflicts between the descriptions, definitions, and / or terminology used in the supplementary materials of this application and the content of this application, the descriptions, definitions, and / or terminology used in this application shall prevail.
[0061] Finally, it should be understood that the embodiments described in this application are merely illustrative of the principles of the embodiments of this application. Other modifications may also fall within the scope of this application. Therefore, alternative configurations of the embodiments of this application are considered as examples and not limitations, and are regarded as consistent with the teachings of this application. Accordingly, the embodiments of this application are not limited to the embodiments explicitly described and illustrated in this application.
Claims
1. A method for preparing a water-based varnish that is abrasion-resistant and phenol-yellowing-resistant for clothing hang tags, characterized in that, Includes the following steps: S1. Add the waterborne polyurethane dispersion and the acrylic modified organosilicon emulsion to the reactor according to the preset mass ratio, and stir under nitrogen protection to form a composite resin base. S2. Based on the technical requirements of wear resistance and phenolic yellowing resistance, functional additives are added synergistically and stirred until homogenized; S3. Heat to 65-75℃, slowly add the fluorinated acrylate monomer mixture, and simultaneously add the photoinitiator TPO, and carry out in-situ graft polymerization under UV irradiation; S4. The mixture is treated with a high-shear disperser, and supercritical carbon dioxide fluid is injected simultaneously. S5. Collect parameter data of gloss, abrasion resistance coefficient and phenol yellowing inhibition rate of the sample in real time, and determine whether the sample is qualified based on the parameter data; Specifically, step S5 includes the following sub-steps: S5.
1. Obtain parameter data in real time through an online monitoring system: the parameter data includes gloss, abrasion resistance coefficient and phenol yellowing inhibition rate; S5.2 Calculate the difference based on the parameter data and the target threshold: Wear resistance deviation δ1 = Wear resistance coefficient - First target threshold Phenolic yellowing deviation δ2 = Phenolic yellowing inhibition rate - Second target threshold; S5.
3. Determine whether the sample is qualified based on the gloss and the difference; if qualified, the final sample is obtained and discharged; if unqualified, proceed to step S5.
4. S5.4 Calculate the preparation parameter compensation amount based on the difference, and perform the corresponding compensation operation based on the compensation amount, and then repeat steps S5.1-S5.
3.
2. The method for preparing a wear-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags according to claim 1, characterized in that, In step S1, the mass ratio of the aqueous polyurethane dispersion to the acrylic modified silicone emulsion is 5:3; the stirring conditions are 400-600 rpm for 10-15 min, and the nitrogen flow rate is 2-3 L / min.
3. The method for preparing a wear-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags according to claim 1, characterized in that, The functional additives in step S2 include: a) Nano-sized silica sol, added at 3-5% of the total weight of the system; b) Cyclodextrin-modified β-zeolite molecular sieve with a pore size of 0.6-0.8 nm and an addition amount of 1.5-2.5%; c) A composite light stabilizer consisting of hindered amine 770 and benzotriazole UV-326, added at an amount of 0.8-1.5%.
4. The method for preparing a wear-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags according to claim 1, characterized in that, In step S3: The fluorinated acrylate monomer mixture contains dodecafluoroheptyl methacrylate and hexafluorobutyl acrylate in a mass ratio of 3:
1. The amount of photoinitiator TPO added is 1.5-2.5% of the total weight of the monomers; UV irradiation intensity is 300-400 mW / cm² 2 , wavelength 365nm.
5. The method for preparing a wear-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags according to claim 1, characterized in that, The injection of supercritical carbon dioxide fluid in step S4 satisfies the following: Critical pressure: 7.4-8.2 MPa; temperature: 35-40℃. The injection rate is 10-15% of the system volume / min; The high-shear disperser operates at a speed of 10,000-15,000 rpm.
6. The method for preparing a wear-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags according to claim 5, characterized in that, In step S5.2: The first target threshold is a wear resistance coefficient of 0.85; The second target threshold is a phenolic yellowing inhibition rate of 92%.
7. The method for preparing a wear-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags according to claim 6, characterized in that, The qualification determination in step S5.3 requires the following conditions to be met simultaneously: δ1≥0, δ2≥0, gloss ≥94GU.
8. The method for preparing a wear-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags according to claim 7, characterized in that, The compensation operation in step S5.4 includes: When δ1 < -0.05, add nanodiamond dispersion, the amount added is... When δ2 < -3%, add an ionic liquid phenol scavenger, with the addition amount Q (%) = 0.5 × log (10 × |δ2|).
9. The method for preparing a wear-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags according to claim 8, characterized in that, The ionic liquid trapping agent is 1-butyl-3-methylimidazolium tetrafluoroborate, which, upon addition, synchronously regulates the supercritical CO2 flow rate. When the viscosity change rate is >10% / min, the flow rate increases by 15-20%; When the viscosity change rate is <5% / min, the flow rate decreases by 10%.
10. The method for preparing a wear-resistant and phenol-yellowing-resistant water-based varnish for garment hang tags according to claim 1, characterized in that, In step S5.1: Gloss was measured online using a 60° incident angle spectrometer. The wear resistance coefficient is estimated in real time based on rheometer data and a particle concentration correlation model; The inhibition rate of phenol yellowing was calculated by measuring the attenuation rate of the characteristic peak of phenol using ultraviolet spectroscopy.